185 Cannabis Dependence and Health Care Utilization Following Cervical and Lumbar Spine Fusions: National Database Analysis. (April 2023) - Alkin, Victoria; Dietz, Nicholas; Sharma, Mayur; Drazin, Doniel
Abstract : INTRODUCTION: Recent increases in cannabis use have been associated with broader legalization and social acceptance. Smoking tobacco leads to a higher incidence of pseudoarthrosis and complications following spinal fusion. However, little research has been done regarding the impact of cannabis on outcomes following spine fusions. METHODS: The IBM MarketScan Database (2009-2019) was used to identify patients who underwent single or multilevel cervical or lumbar fusions. Patients were categorized based on cannabis abuse disorder. Inpatient hospitalization outcomes (length of stay, discharge disposition, complications, payments), post-discharge outcomes (reoperation, readmission, outpatient services, medication refills, payments), and complications were analyzed at 6- and 12- months following index procedure. Exact match was used to control for unbalanced demographics. SAS 9.4 was used for data analysis. RESULTS: The exact match cohort had 2958 cervical fusion patients (1479 with a cannabis-related disorder) and 3204 lumbar fusion patients (1602 with a cannabis-related disorder). For cervical fusion, no significant difference between patients with and without cannabis-related disorder was found for most peri- and postoperative complications, overall complications, or discharge home. Users had significantly higher occurrence of sepsis (1.1% vs 0.3%, P = 0.0073) and significantly lower hospitalization payments ($18541 vs. $21137, P=0.0019). For lumbar fusion, no difference was found for overall complications or specific peri- and postoperative complications. Users had significantly lower hospitalization payments ($22612 vs. $29013, P = 0.0002). In both the cervical and lumbar groups, no differences were found in reoperation. Opioid use was lower for users directly post-operation, but higher 3-12 months post-operation. CONCLUSIONS: Cannabis dependence and abuse disorders are not associated with worsened perioperative outcomes in patients undergoing single or multilevel cervical or lumbar fusions.